The DiskMass Survey. XI. Disk Geometries and Star Formation Surface Densities from Ionized Gas Kinematics and Line Intensities for the Full Hα Sample - Robert A. Swaters; David R. Andersen; Matthew A. Bershady; Thomas P. K. Martinsson; Paul Scholz; Marc A.W. Verheijen; Kyle B. Westfall (The Astrophysical Journal Supplement Series)
We present H α -region integral-field spectroscopy for 137 low-inclination, intermediate to late-type galaxies. Spectroscopic data, obtained with SparsePak and the Bench Spectrograph on the WIYN 3.5 m telescope, span 6475–6880 Å with an instrumental resolution of 13 km s ^−1 ( σ ). The spectral range includes H α and [N ii ] λλ 6548, 6584 for every source, and in most cases includes [S ii ] λλ 6717, 6731. We present and publicly release 18,288 calibrated spectra and visually inspected Gaussian line fits to the H α emission. Most measurements yield a signal-to-noise ratio above 5 in integrated H α line flux, adequate to derive reliable line centroids and widths. Second kinematic components are required to adequately describe the emission-line profile in 15% of reliable data. The H α velocity dispersion distribution peaks at 18 km s ^−1 , modestly increasing with H α surface brightness, reaching 20 km s ^−1 at Σ _H _α = 10 ^40 erg s ^−1 kpc ^−2 . Lower-flux secondary components, when present, have widths of ~50 km s ^−1 . These results agree well with previous echelle measurements of nearby galaxies. Velocity-field analysis yields kinematic inclinations, with a sample mean of 26°. Large kinematic asymmetries systematically affect kinematic inclination estimates in a small fraction of our sample. When deviations from circular motion are below 10% of the projected velocity, kinematic inclinations are consistent, within errors, to estimates from inverting the Tully–Fisher relation. This confirms previous disk-submaximality estimates for galaxies with regular kinematics based on inclinations derived from inverting the Tully–Fisher relation.